Implementasi Peraturan Walikota Denpasar Nomor 9 Tahun 2009 Tentang Penataan dan Pembinaan Pasar Tradisional, Pusat Perbelanjaan dan Toko Modern - Ni Kadek Diah Sri Laksmi Dewi; Ni Luh Mahendrawati; Desak Gde Dwi Arini (Jurnal Analogi Hukum, 2021)
he development of the business world in Indonesia is fairly rapid, one of which is a network retail business or minimarket, so it spurs a variety of new problems relating to the practice of business activities in the field. So that the government must be able to make a regulation in order to prevent and overcome problems that will or are arising. The problems of this study are: 1) How to structuring and fostering traditional markets, shopping centers and modern stores based on Denpasar Mayor Regulation Number 9 of 2009 and 2) Does the existence of modern stores lead to monopolistic practices and unfair business competition. The research method used is the method of empirical legal research so that the problem approach used is a sociological or research approach with the aim of obtaining legal knowledge by plunging directly into the objectThe results of the study can be concluded that the Mayor of Denpasar Regulation Number 9 of 2009 concerning the Arrangement and Development of Traditional Markets, Shopping Centers, and Modern Stores does not make clear rules for minimarket businesses, so that if the development of the minimarkets is allowed to continue without any rules binding will become the center of monopolistic practices that have the potential to undermine fair business competition between traditional market traders and modern shop business people as well as between modern store business actors.